PENINGKATAN KECERDASAN VISUAL SPASIAL MELALUI BERMAIN MIND MAPPING - FADHILAH LATIEF (PEDAGOGIKA, 2018)
The objectives of this research is to improve the visual-spatial intelligence of children through playing mind mapping. This research was carried out in group Raudhatul Athfaal Mardhati, Makassar with 13 subject , on the month from April to May 2017. This research uses an action research design model of Kemmis and Mc Taggart, through two cycles consisting of seven meetings on the first cycle and six meetings on the second cycle which includes the stages of planning, action, observation and reflection. Data analysis using quantitative and qualitative analysis. Data obtained by referring to the research instrument which refers to the visual-spatial intelligence. The results showed an increase in visual-spatial intelligence scores of children with the acquisition of visual-spatial intelligence classical pre-action reached 49.25%, the first cycle increased the score reached 75.15% and the second cycle was obtained which satisfy the classical score reached 88.28% so it can be concluded that the